Analysis of the Genome Architecture of Lacticaseibacillus paracasei UNQLpc 10, a Strain with Oenological Potential as a Malolactic Starter - Iglesias, Nestor Gabriel (2022)
The Lacticaseibacillus paracasei UNQLpc 10 strain was isolated from a Malbec wine produced in North Patagonia, Argentina, and identified by 16S rRNA gene sequencing. The aim of this work was to obtain the fully assembled genome of the UNQLpc 10 strain, analyze its structure, and evaluate the possible functions of the predicted genes with regard to its oenological potential as a malolactic starter. UNQLpc10 is the first whole assembled genome of an oenological strain of Lcb. paracasei reported in databases. This information is of great interest inexpanding the knowledge of diversity of oenological lactic acid bacteria and in searching for new candidate species/strains to design starter cultures. The in silico genome-wide analysis of UNQLpc 10 confirms the existence of genes encoding enzymes involved in the synthesis of several metabolites of oenological interest, and proteins related to stress responses. Furthermore, when UNQLpc 10 was incubated in synthetic wine, it exhibited a very good survival and L-malic acid consumption ability.